2021
DOI: 10.1155/2021/9936872
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Gas Production Performance in Methane Hydrate of Multilateral Well under Depressurization in Krishna-Godavari Basin

Abstract: Nature gas hydrate is a new kind of clean and potential resources. Depressurization is regarded as the most effective and promising hydrate production technology. One of the key points in improving the gas production effectiveness of depressurization is whether pressure gradient could transmit in strata effectively. Single well method is widely used in hydrate exploit which is circumscribed in expanding the range of hydrate decomposition. Consequently, the well structure and production strategy needs to be opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Therefore, extracting hydrates from complex structured wells has become a research hotspot. For example, Xin X. et al found that the deployment depth of the lateral branches in a multilateral well is the key factor affecting production capacity [13]. Mao P. et al evaluated the influence of different parameters related to helical multilateral well on production capacity and believed that it had the potential to achieve commercial development of natural gas hydrates [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extracting hydrates from complex structured wells has become a research hotspot. For example, Xin X. et al found that the deployment depth of the lateral branches in a multilateral well is the key factor affecting production capacity [13]. Mao P. et al evaluated the influence of different parameters related to helical multilateral well on production capacity and believed that it had the potential to achieve commercial development of natural gas hydrates [14].…”
Section: Introductionmentioning
confidence: 99%